Customer360 Platforms in Retail and CPG: A Data-Driven Analysis of Enterprise-Scale Personalization Infrastructure - Vikas Sripathi (International Journal of Computational and Experimental Science and Engineering, 2026)
Personalization has shifted from a competitive differentiator to a baseline requirement in modern retail and consumer packaged goods (CPG) markets. Despite high organizational confidence in digital experiences, a persistent gap remains between internal assessments and actual customer perceptions. This article synthesizes recent industry evidence to examine Customer360 platforms as the foundational infrastructure for large‑scale personalization, focusing on enterprise loyalty programs, streaming data architectures, and cloud data warehousing patterns. Documented cases from grocery retail show loyalty membership in the tens of millions, double‑digit digital sales growth, and sustained multi‑year loyalty expansion, illustrating the scale at which Customer360 platforms now operate. Technical analysis of cloud publish–subscribe systems and data warehouse adoption highlights concrete throughput limits, message constraints, and retention policies that shape architectural decisions. Industry studies further quantify the economic impact of personalization, with average revenue uplifts, higher per‑transaction spend, and large, recurring costs from poor data quality and security breaches. Taken together, these findings argue that data quality controls and security safeguards in Customer360 programs are financially material design requirements rather than discretionary best practices.